Differential Prognosis of True Bifurcation Lesions According to Left Main Versus Non–Left Main Location and Treatment Strategy - Ki Hong Choi; Chang‐Wook Nam; Francesco Bruno; Yun‐Kyeong Cho; Leonardo De Luca; Jeehoon Kang; Alessio Mattesini; Young Bin Song; Alessandra Truffa; Hyo‐Soo Kim; Wojciech Wańha; Woo Jung Chun; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Although true bifurcation lesions are associated with a high risk of procedural complications, the differential prognostic implications of percutaneous coronary intervention for true bifurcations according to lesion location are unclear. This study aimed to identify whether clinical outcomes of true bifurcation lesions differed between left main coronary artery (LM) and non‐LM bifurcations and to determine the optimal treatment strategy for subtypes of bifurcation lesions in the current‐generation drug‐eluting stent era. Methods The ULTRA‐BIFURCAT (Combined Insights From the Unified COBIS III, RAIN, and ULTRA Registries) was created by merging 3 bifurcation‐dedicated registries from Korea and Italy. For this, 6548 patients treated with bifurcation lesions were stratified by lesion location and subtype. The primary end point was major adverse cardiac events (MACEs; composite of all‐cause death, myocardial infarction, target lesion revascularization, and stent thrombosis) at 800 days. Results In patients with an LM bifurcation, those with a true bifurcation had a significantly higher risk of a MACE than those with a nontrue bifurcation (20.2% versus 13.4%, adjusted hazard ratio [HR], 1.44 [95% CI, 1.11–1.86]; P=0.006). Conversely, there was no significant difference in the risk of a MACE according to true versus nontrue bifurcation in patients with non‐LM bifurcation lesions (9.0% versus 8.8%; adjusted HR, 1.02 [95% CI, 0.82–1.27]; P=0.849). For LM true bifurcations, MACE rates were comparable between 1‐stent and 2‐stent strategies, whereas for LM nontrue bifurcations, the 2‐stent strategy was associated with a significantly higher risk of MACEs than the 1‐stent strategy. No significant differences in the risk of MACEs were observed in non‐LM bifurcation lesions according to lesion subtype or treatment strategy. Conclusions Clinical outcomes were worse for LM true bifurcation lesions than non‐LM true bifurcation lesions. A provisional 1‐stent strategy should be the preferred approach for treating LM nontrue bifurcation lesions. Registration URL: https://www.clinicaltrials.gov; Unique identifier: NCT03068494, NCT03544294, and NCT05205148.